Use of waste tyre rubber in enhancing the mechanical properties of stone mastic asphalt mix / Nuha S. Mashaan - Nuha, S. Mashaan (2016)

(untitled)
An immense problem affecting environmental pollution is the unprecedented increase of waste tyre vehicles. Furthermore, rapid economic and industrial growth generates increasing amounts of waste materials includes millions of waste tyre rubber. The lack of proper controlled use of these waste would lead to added disposal costs, increase illegal dumping or inadequate storage and could increase the risk of fire and environmental damage. In this research, attempts to inspire a green technology which is more environmentally friendly that can produce economic value are a major consideration in the utilization of waste tyre rubber in the form of Crumb Rubber Modifier (CRM) in asphalt concrete. In asphalt concrete technology, there are two method to use CRM for asphalt road construction either as a binder modifier (wet process) or as an aggregate (dry process). The dry process has been a far less popular method as compared to the wet process which contributed to inconsistent field performance. The primary aim of this study was to investigate the effect of adding waste tyre rubber as an additive to Stone Mastic Asphalt (SMA) mixture performance properties using the dry process. The research project had three phases. In the first phase, Marshall test was conducted on mixtures containing different percentages of crumb rubber with different bitumen content. The optimum bitumen content was incorporated to design the CRM-reinforced-SMA. In the second phase, the mechanical properties in term of stiffness modulus, fatigue, creep, drain-down, moisture susceptibility and resistance to rutting of CRM-reinforced-SMA were investigated and compared with non-reinforced- SMA. Finally, in last phase, an assessment and evaluation of the relationship between the stiffness and dynamic creep with respect to rutting deformation and fatigue life of SMA reinforced with crumb rubber. Additionally, predicting asphalt pavement performance is an important matter which iv can save cost and energy. To ensure an accurate estimation of performance of the mixtures, new soft computing techniques had been used. The results showed that the resilient modulus of CRM-reinforced-SMA samples were obviously higher in comparison with that of unmodified samples. The resistance of waste tyre rubber in producing horizontal tensile stresses attenuated the production of vertical cracks and deterred these cracks from diffusing along the diameters of the asphalt samples. This in turn improved the fatigue life of reinforced samples. The results show that the addition of CRM into the mixture has an obvious significant effect on the performance properties of SMA which could improve the mixture’s resistance against permanent deformation. Further, higher correlation coefficient was obtained between the rut depth and permanent strain, and, also higher correlation coefficient between fatigue and resilient modulus. Soft computing methodologies had shown a very good learning and prediction capabilities and indicated the most significant effect on stiffness performance.